DINAMIKA PERUBAHAN TUTUPAN LAHAN HUTAN LINDUNG KECAMATAN MORAMO (2003–2023) BERDASARKAN ANALISIS CITRA LANDSAT: Dynamics of Land Cover Change in the Protected Forest of Moramo Subdistrict (2003–2023) Using Landsat Imagery - Sahindomi Bana; Basrudin; Herlina Hakim (Jurnal Celebica : Jurnal Kehutanan Indonesia, 2025)
This study aims to analyze land cover changes in the protected forest area of Moramo Subdistrict, South Konawe Regency, using Landsat satellite imagery from 2003, 2014, and 2023 through supervised classification methods and spatial analysis with ArcGIS 10.8. The Moramo protected forest plays a vital role in maintaining ecological balance; however, community activities that convert forest land into agricultural land have triggered significant land cover changes. The results identified five main land cover classes: primary dryland forest, secondary dryland forest, mixed dryland agriculture, shrubland, and bare land. Between 2003–2014, the largest decrease occurred in primary dryland forest, with a loss of 556.27 ha, while mixed dryland agriculture increased by 437.31 ha. During 2014–2023, primary dryland forest decreased by 244.87 ha, while mixed dryland agriculture expanded by 197.26 ha. Classification accuracy testing showed an overall accuracy of 84% and a kappa accuracy of 82.61%, indicating a reliable level of classification performance. The study concludes that land cover change in Moramo protected forest is mainly driven by the conversion of primary and secondary dryland forests into agricultural land. This condition potentially reduces the ecological functions of the forest, increases the risk of erosion and flooding, and decreases environmental quality. Therefore, regular monitoring and the implementation of social forestry programs are needed to preserve the forest while providing legal benefits to surrounding communities Keywords: land cover, protected forest, Landsat imagery, spatial analysis, Moramo.